The Systemic Lupus Erythematosus Infection Predictive Index (LIPI): A Clinical-Immunological Tool to Predict Infections in Lupus Patients - Torres-Ruiz, Jiram; Mejía-Domínguez, Nancy R.; Zentella-Dehesa, Alejandro; Ponce-de-León, Alfredo; Morales-Padilla, Sandra Rubí; Vázquez-Rodríguez, Ricardo; Alvarado-Lara, Mario René; Reyna-de-la-Garza, Roberto Adrián; Tapia-Rodríguez, Miguel; Juárez-Vega, Guillermo; Merayo-Chalico, Javier; Barrera-Vargas, Ana; et al. (Frontiers in Immunology, 2019)
Among autoimmune diseases, systemic lupus erythematosus (SLE) patients have a unique predisposition to develop infections, which represents one of their main causes of morbidity and mortality. Many infections occur at disease diagnosis in the absence of immunosuppressive therapy, suggesting that the immunological abnormalities in SLE patients might be fundamental for the development of this complication. The aim of this study was to address the main clinical and immunological features associated with the development of infection and to create and validate a compound clinical-immunological infection predictive index in a cohort of SLE patients. We included 55 SLE patients with < 5 years since diagnosis. The clinical and immunological features were evaluated periodically and patients were followed-up during 1 year, searching for the development of infection. Immunophenotyping was performed by multiparametric flow cytometry and neutrophil extracellular traps (NETs) were assessed by confocal microscopy. Eighteen patients (32.7%) presented 19 infectious events, 5 (26.3%) were severe. For the construction of the index, we performed a logistic regression analysis and the cutoff points were determined with ROC curves. Increased numbers of peripheral Th17 cells, B cell lymphopenia, and lower TLR2 expression in monocytes, as well as the use of cyclophosphamide were the major risk factors for the development of infection and thus were included in the index. Besides, patients that developed infection were characterized by increased numbers of low-density granulocytes (LDGs) and higher expression of LL-37 in NETs upon infection. Finally, we validated the index retrospectively in a nested case-control study. A score >1.5 points was able to predict infection in the following year (AUC = 0.97; LR– = 0.001, specificity 100%, P = 0.0003). Our index encompasses novel immunological features able to prospectively predict the risk of infection in SLE patients.